Estudio de factibilidad para la creación de una empresa destinada a producir y comercializar una compota con base en la fruta de arazá (Eugenia stipitata) ubicada en la ciudad de Armenia. (2012)
The project is to conduct a feasibility study after seeing an opportunity to encourage the growing in the department of Quindio, the crops are located in the municipality of Montenegro and Pueblo Tapao. These crops for their weather conditions of 1294 at 21 ° C, besides nowadays; women who are mothers and work, look for products which supplement food. A study was conducted to analyze the market and its result is not to launch the product in the supermarket distribution channel for their competence that it has, from then; we analyzed the channel store to store taking advantage of the division in the Municipality of Armenia, the population who will benefit is of 18,407 children from 6 months old to 3 years old, its presentation will be in a glass container with metal lid cover commonly call button, to know well the vacuum exhaust and help maintain the life of the product. A field study was conducted to analyze the market, the offer, to know likes, preferences, capacity of buying, measuring the degree of behavior, acceptance and expectations towards the product, applying techniques such as; surveys, interviews, visits, and focal group. Similarly, the compote arazá be developed in the pilot plant foods Quindío University since it counts as strength not to incur the costs of purchasing equipment, is this plant has the rental service of machinery for product development.